Influence of impurities on the absorption spectrum of thin Cs₄PbI₆ films - Yunakova, O.N.; Miloslavskii, V.K.; Kovalenko, E.N.; Kovalenko, V.V. (Functional Materials, 2014)
The absorption spectrum of the solid solutions,i (Cs₁₋xMx)₄PbI₆ (M = Rb,K) 0≤x≤1 is studied in the spectral range 2-6 eV at T = 90 K. The formation of solid solutions (Cs₁₋xMx)₄PbI₆ in all range of concentrations, but (Cs₁₋xMx)₄PbI₆ in the range 0≤x≤0.9 is established, the compound K₄PbI₆ is unstable. Linear concentration of long-wavelength exciton band parameters in the (Cs₁₋xMx)₄PbI₆ indicates the localization of excitons in PbI₆⁴⁻ structural elements of the compounds crystal lattice.